Dynamics of Civil Structures, Volume 2 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Pakzad, Shamim; Juan, Caicedo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Dynamics of Civil Structures, Volume 2. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the second volume of ten from the Conference brings together contributions to this important area of research and engineering. Th e collection presents early fi ndings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Modal Parameter Identifi cation • DynamicTesting of Civil Structures • Human Induced Vibrations of Civil Structures • Model Updating • Operational Modal Analysis • Damage Detection • Bridge Dynamics • Experimental Techniques for Civil Structures • Hybrid testing • Vibration Control of Civil Structures.
1 Damage Assessment of Steel Structures Using Multi-Autoregressive Model -- 2. Damage Detection with Symplectic Geometry Spectrum Analysis in Changing Enviroments -- 3 Compressive Sensing Strategies for Multiple Damage Detection and Localization -- 4 Structural Damage Detection Through Vibrational Feature Analysis with Missing Data -- 5 Damage Detection Optimization Using Wavelet Multiresolution Analysis and Genetic Algorithm -- 6 A Novel Acoustoelastic-based Technique for Stress Measurement in Structural Components -- 7 Non-model-based Damage Identification of Plates Using Curvature Mode Shapes -- 8 A Machine Learning Framework for Automated Functionality Monitoring of Movable Bridges -- 9 Development of an Acoustic Sensing Based Structural Health Monitoring Technique for Wind Turbine Blades -- 10 Making Structural Condition Diagnostics Robust to Environmental Variability -- 11 Damage Location by Maximum Entropy Method on a Civil Structure -- 12 Exploring Environmental and Operational Variations in SHM Data Using Heteroscedastic Gaussian Processes -- 13 Vibration Testing for Bridge Load Rating -- 14 Finite Element Model Updating of French Creek Bridge -- 15 Damage Detection of a Bridge Model After Simulated Ground Motion -- 16 Bridge Assessment Using Weigh-In-Motion and Acoustic Emision Methods -- 17 Model-based Estimation of Hydrodynamic Forces on the Bergsoysund Bridge -- 18 Operational Modal Analysis and Model Updating of Riveted Steel Bridge -- 19 Finite Element Model Updating of Portage Creek Bridge -- 20 Full-scale Measurements on the Hardanger Bridge During Strong Winds -- 21 Multi-Shaker Modal Testing and Modal Identification of Hollow-Core Floor System -- 22 Hybrid Time/Frequency Domain Identification of Real Base-Isolated Structure -- 23 The use of OMA for the Validation of the Design of the Allianz Tower in Milan -- 24 Vibration Transmission Through Non-Structural Partitions Between Building Floor Levels -- 25 Inelastic Base Shear Reconstruction from Sparse Acceleration Measurements of Buildings -- 26 Genetic Algorithm use for Internally Resonating Lattice Optimization: Case of a Beam-like Metastructure -- 27 Design of Metamaterials for Seismic Isolation -- 28 Transfer Length Probabilistic Model Updating In High Performance Concrete -- 29 Seismic Behavior of Partially Prestressed Concrete Structures -- 30 Ambient Vibration Testing of A Super Tall Building In Shanghai -- 31 Ambient Vibration Testing Of Two Highly Irregular Tall Buildings In Shanghai -- 32 Estimating Effective Viscous Damping and Restoring Force in Reinforced Concrete Buildings -- 33 Structural Assessment of a School Building in Sankhu, Nepal Damaged Due to Torsional Response During the 2015 Gorkha Earthquake.
Keywords: Civil engineering; Mechanics, Applied; Solids; Multibody systems; Vibration; Civil Engineering; Solid Mechanics; Multibody Systems and Mechanical Vibrations